Ecological transcriptomics reveals stress response pathways of a ground-herb species in a waterlogging gradient of Amazonian riparian forests - Palma-Silva, Clarisse; Mortati, Amanda F.; Chaves, Cleber Juliano Neves; Simões Santos Leal, Bárbara; Ribeiro, Rafael V.; Pinheiro, Fabio; Ferro, Milene [UNESP]; Riaño-Pachón, Diego M.; de Mattos, Jacqueline Salvi; Tavares, Marília Manupella; Aecyo, Paulo; da Costa Cacossi, Tami; et al. (Wiley, 2024)
Environmental stress is a fundamental facet of life and a significant driver of natural selection in the wild. Gene expression diversity may facilitate adaptation to environmental changes, without necessary genetic change, but its role in adaptive divergence remains largely understudied in Neotropical systems. In Amazonian riparian forests, species distribution is predominantly influenced by species' waterlogging tolerance. The flooding gradient delineates distinct wetland forest types, shaping habitats and species characteristics. Here we investigated the molecular basis of environmental stress response in a tropical ground-herb species (Ischnosiphon puberulus) to environmental variation in Amazonian riparian forests. We compared environmental variables and gene expression profiles from individuals collected in two forest types: Igapó and Terra firme in the Amazonian riparian forests. Predictable seasonal flooding poses a significant challenge in Igapó compared to Terra firme environments, with the former presenting higher water column height and longer flooding duration. Our findings suggest that contrasting environmental conditions related to flooding regimes are important drivers of population genetic differentiation and differential gene expression in I. puberulus. Enriched gene ontology terms highlight associations with environmental stresses, such as defence response, water transport, phosphorylation, root development, response to auxin, salicylic acid and oxidative stress. By uncovering key environmental stress response pathways conserved across populations, I. puberulus offers novel genetic insights into the molecular basis of plant reactions to environmental constraints found in flooded areas of this highly biodiverse neotropical ecosystem.
Keywords: adaptation; Amazonian forest; differential gene expression; Neotropical biomes; population genetics – empirical